Calcium peroxide eliminates grease inhibition and promotes short-chain fatty acids production during anaerobic fermentation of food waste. (November 2020) - Xu, Qing; Du, Mingting; Liu, Xuran; Wang, Dongbo; Wu, Yanxin; Li, Yifu; Yang, Jingnan; Fu, Qizi; He, Dandan; Feng, Chongling; Liu, Yiwen; Wang, Qiling; et al.
Graphical abstract: Highlights: CaO2 effectively eliminated the inhibitory effect of grease on SCFAs production. SCFAs yield from food waste fermentation was further promoted with CaO2 . CaO2 facilitated biodegradable organics release and improved grease degradation. OH – and Ca 2+ played a vital role in SCFAs production improvement. O2 – and OH radicals were the main contributors to grease degradation. Abstract: Deterioration of anaerobic fermentation can occur with the presence of grease in food waste, but little information on eliminating this deterioration is currently available. In this study, it was found that the presence of 10 g/L grease decreased SCFAs production from 16.97 to 13.32 g COD/L and prolonged the optimal fermentation time to 7 days, but could be respectively recovered to 39.10 g COD/L and 4 days with 0.02 mg/g VS (volatile solids) calcium peroxide addition. Mechanism investigations indicated that calcium peroxide facilitated biodegradable organics release and improved grease degradation, thereby providing enough nutrients and better growth environments to microbes for SCFAs-producing, which could be further supported by the elevated enzymes activities responding to hydrolysis and acidification process. Further investigations revealed that among the main derivates of calcium peroxide, OH – and Ca 2+ played vital role in SCFAs production promotion, O2 – and OH radicals were the main contributors to grease degradation.